(untitled) (Global Journals of Research in Engineering, 2024)
This study presents a comprehensive analysis of the preparedness and knowledge of firefighters in Kuwait regarding electric vehicle EV accidents Using a multi-method approach that includes surveys literature reviews statistical data and interviews with emergency responders and municipal officials in Sweden the study compares EV preparedness in Kuwait with that in selected European countries Norway Iceland and Sweden The findings reveal significant gaps in training and knowledge among Kuwait firefighters indicating an urgent need for enhanced training programs and standardized protocols Best practices from European countries such as specialized training programs and advanced detection equipment are highlighted as potential solutions for improving safety and preparedness in Kuwait The study aims to enhance readiness for the increasing adoption of EVs ensuring the safety of responders and the public Key recommendations include the development of comprehensive training programs establishment of standardized protocols investment in specialized equipment and fostering international collaboration Future research directions are also suggested to further improve EV accident management